THE DYNAMIC OF POWER RELATIONS OVER BOMBANA'S GOLD MINING IN SOUTEAST SULAWESI INDONESIA - Ulil Amri (Universitas Gadjah Mada, 2011)
In mid-2008 a new gold mining site was discovered in bombana Regency